(untitled) (Ekonomski vjesnik/Econviews - Review of Contemporary Business, Entrepreneurship and Economic Issues, 2016)
The paper shall present the results of the research that was aimed at measuring employee satisfaction with the existing state of affairs as well as their expectations in the future in the case of the Economic and Financial Affairs Department of the Croatian Pension Insurance Institute (CPII), Regional Office (RO) Osijek. The study was conducted by using the KVALIMETAR measuring instrument. The results of the study allowed the identification of critical areas in the management system through the dimensions of the KVALIMETAR measuring instrument, based on which recommendations for improvement were made. A negative gap was recorded in all dimensions, which leads to the conclusion that the existing state of affairs should not be maintained. It is also necessary to continue to work and invest further efforts to improve quality since it is precisely continuous improvement and upgrading that quality management mandates. Keywords: Quality, quality management, measuring instrument, employee satisfaction